Analysis of Financial Performance in Dairy Enterprises; The Case Study of Konya, Turkey - Cennet Oğuz; Aysun Yener (Turkish Journal of Agriculture: Food Science and Technology)
Sustainability and development of the dairy enterprises are dependent on competitiveness. Determination of the performance of the enterprises requires measurement and analyses of the financial performance of the enterprises. The ability of dairy enterprises to continue and grow is dependent on competitiveness. It requires that the financial performance of the farm enterprises be measured and analysed in order for the enterprises to be able to detect the competition power in a healthy manner. The aim of the study is to analyse the financial performance of the dairy enterprises in Konya province by determining the capital structure. Çumra, Karapınar and Ereğli districts constituted 15% of the number of bovine animals, were selected by using sampling method. The number of dairy cattle in these enterprises constituted the main frame of the population the primary data collected from 125 dairy farm enterprises with questionnaire technique through stratified sampling method with 95% confidence interval and error margin of 5%. The capital structure of the enterprises surveyed in the research area was classified according to their functions and the average active capital of the enterprises was calculated as 845,330.85$. 67.87% of the active capital is composed of land capital, 31.70% is composed of fixed enterprises capital and 0.43% is variable working capital. The economic profitability level (EP) was determined as 6.90% and the financial profitability level (FP) indicated the success of the enterprise was calculated as 7.06%. The capital turnover rate, an important indicator in the success and comparison of the enterprises, is 28.22%. As a result, their development and competitiveness are slow, because they do not use enough business and investment capital.